Measuring the Impact of Learning Organization on Employees’ Job Satisfaction in Guangdong Private-owned Knowledge-and-technology-intensive Firms - Chengzhi, Zhou (2019)
In order to search for an effective way to help the knowledge-and-technology-intensive firms in the private sector of the Guangdong Province of China to solve the problem of being lack of competitiveness in innovation and creativity, and based on the previous literature, a well-established learning organization can increase and maintain the competitiveness of the above two areas while having positive effects on employees’ organizational performance and job satisfaction etc. which these factors are all beneficial to the development of the organizations. Given the circumstance that there are no related studies about the effect of the perception of learning organization towards employees’ job satisfaction in these firms before. As a result, this empirical study aims to investigate the employees’ perception of LO towards their extrinsic, intrinsic and general job satisfaction due to being lack of relevant research before.